PRINCIPLES OF OPTIMAL PLANNING OF EXPERIMENTALLY THEORETICAL RESEARCHES OF BUILDING CONSTRUCTIONS - A. I. Akaev; M. G. Magomedov; M. A. Hanmagomedov (Вестник Дагестанского государственного технического университета: Технические науки)
Basic principles of optimal organization of researches of building constructions working in composition the bearing systems of building are generalized in the article, taking into account the necessity of comparison of theoretical and experimental results on adequate basis. Methodology of mutual rapprochement of calculation charts and terms of realization of experiment offers with the observance of main principle - acceptable to practice accordance of charts of theoretical and experimental research to the actual terms of work of constructions in building.